Porosity characterization and respective influence on short-beam strength of advanced composite processed by resin transfer molding and compression molding - Santos, Ana Carolina Mendes Quintanilha Silva [UNESP]; Monticeli, Francisco Maciel [UNESP]; Ornaghi, Heitor [UNESP]; Santos, Luis Felipe de Paula [UNESP]; Cioffi, Maria Odila Hilário [UNESP] (SAGE Publications, 2020)
This work has been developed for a comparative purpose concerning the processing and respective mechanical performance of CFRP composites processed by resin transfer molding (RTM) and compression molding (CM) techniques. Thermal and viscosimetric tests before processing certified the optimal parameter procedure. Both composites were submitted to short-beam shear tests and through microscopy to determine failure mechanisms. CM specimens presented a decrease of 27% in shear strength caused by the presence of macro porosity that induced crack initiation and connection of different delamination plies, causing the speeding up of crack propagation and jump of the interlaminar layer. The low capillary effect and higher viscous force were responsible for macro porosity, inducing heterogeneous impregnation in CM and to the direction reduce in mechanical behavior. On the other hand, more homogeneous impregnation in RTM specimens was responsible for the absence of macro porosity, ensuring higher values of shear strength and lower void volume fraction.
Keywords: CFRP; compression molding; porosity; resin transfer molding; short-beam strength; Structural composites